The MOSDEF survey: a new view of a remarkable z = 1.89 merger. Issue 3 (8th October 2022) - Runco, Jordan N; Shapley, Alice E; Kriek, Mariska; Cappellari, Michele; Topping, Michael W; Sanders, Ryan L; Kokorev, Vasily I; Price, Sedona H; Reddy, Naveen A; Coil, Alison L; Mobasher, Bahram; Siana, Brian; et al.
ABSTRACT: We present a detailed study of a galaxy merger taking place at z  = 1.89 in the GOODS-S field. Here, we analyse Keck/MOSFIRE spectroscopic observations from the MOSFIRE Deep Evolution Field (MOSDEF) survey along with multiwavelength photometry assembled by the 3D- HST survey. The combined data set is modelled to infer the past star formation histories (SFHs) of both merging galaxies. They are found to be massive, with log10 ( M * /M⊙ ) > 11, with a close mass ratio satisfying the typical major-merger definition. Additionally, in the context of delayed-τ models, GOODS-S 43114, and GOODS-S 43683 have similar SFHs and low star formation rates (log10 (SFR(SED)/${\rm M}_{\odot }\, \rm {yr}^{-1}$ ) < 1.0) compared to their past averages. The best-fitting model SEDs show elevated H δA values for both galaxies, indicating that their stellar spectra are dominated by A-type stars, and that star formation peaked ∼0.5−1 Gyr ago and has recently declined. Additionally, based on SED fitting both merging galaxies turned on and shut off star formation within a few hundred Myr of each other, suggesting that their bursts of star formation may be linked. Combining the SFHs and H δA results with recent galaxy merger simulations, we infer that these galaxies have recently completed their first pericentric passage and are moving apart. Finally, the relatively low second velocity moment of GOODS-S 43114, given its stellar mass suggests a disc-like structure. However, including the geometry of the galaxy in the modelling does not completely resolve the discrepancy between the dynamical and stellar masses. Future work is needed to resolve this inconsistency in mass.